FAKTOR RESIKO GANGGUAN FUNGSI GINJAL PADA PEKERJA BENGKEL LAS DI KOTA PURWOKERTO - Anjar Astuti Ferdhiani; Hernayanti Hernayanti; Bambang Heru Budianto (Scripta Biologica, 2018)
Welding was one of the industry in Purwokerto City. One of the exhaust particulate material from the welding process, this will be the potential occurrence of exposure to workers and caused renal dysfunction. Several risk factors have contributed in caused kidney difunction of workers. This study aims to determine the levels of cadmium metal (Cd), chromium (Cr), lead (Pb) with creatinine and Glomerulus Filtration Rate (GFR). The correlation of risk factors for renal dysfunction with creatinine and GFR. The risk factors that play a major role in caused kidney dysfunction. The method used is cross sectional. Sampling using purposive sampling with giving inform consent to the respondent. Provision of questionnaires and blood sampling as much as 3 ml according to ethical clearens. Measurement of metal content of Cd, Cr and Pb; serum creatinine and LFG levels. Number of respondents 30 people with 95% confidence level. The results showed that levels of Cr, Cd and Pb were 0.049 + 0.12 ppm; 1,029 + 2.38 ppm; 4,933+ 11,66 ppm. Cr levels are still within normal limits with levels but Cd and Pb exceeding the normal threshold. Creatinine levels of 1.867 + 0.446 mg / dl showed higher than normal. Minimum of GFR decrease in welding workers was 44 mL / min / 1.73 m2. Risk factors significantly correlated with creatinine and GFR was levels of Pb (p <0.05). Risk factors that play a major role in caused kidney dysfunction in welding workers in Purwokerto city is Pb content with 12.9% percentage effect on serum creatinine level and 9% effect on Glomerulus Filtration Rate.